2020
DOI: 10.1525/collabra.18184
|View full text |Cite
|
Sign up to set email alerts
|

Proximity and Expectancy Modulate Response Vigor After Reward Omission

Abstract: Both humans and some non-human animals tend to respond more vigorously after failing to obtain rewards. Such response invigoration becomes more pronounced when individuals have increased expectations of obtaining rewards during reward pursuit (expectancy), and when they perceive the eventual loss to be proximal to reward receipt (proximity). However, it was unclear whether proximity and expectancy may have distinct influences on response vigor. To investigate this question, we developed a computerized ’scratch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(44 citation statements)
references
References 60 publications
(121 reference statements)
7
31
6
Order By: Relevance
“…These findings are not in line with those of Gipson et al (2012), who showed that reward omission led to invigorated behavior, which, in turn, was related to negative urgency in their study.Of note, Gipson and colleagues (2012) used an operant conditioning paradigm in which reward omission was unexpected. Thus, expectations might have modulated the effect of reward omission in this case (see also Chen et al, 2020). Nevertheless, our findings are consistent with other research showing no associations or only weak associations between behavioral tasks and self-reported impulsivity facets (Creswell et al, 2019;Cyders & Coskunpinar, 2011Reynolds et al, 2006;Schluter et al, 2018;Sharma et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are not in line with those of Gipson et al (2012), who showed that reward omission led to invigorated behavior, which, in turn, was related to negative urgency in their study.Of note, Gipson and colleagues (2012) used an operant conditioning paradigm in which reward omission was unexpected. Thus, expectations might have modulated the effect of reward omission in this case (see also Chen et al, 2020). Nevertheless, our findings are consistent with other research showing no associations or only weak associations between behavioral tasks and self-reported impulsivity facets (Creswell et al, 2019;Cyders & Coskunpinar, 2011Reynolds et al, 2006;Schluter et al, 2018;Sharma et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Subjective ratings in this study revealed that losses were rated as negative emotional events. This post-loss speeding effect has now been replicated many times (Chen et al, 2020;Eben et al, 2022;Eben et al, 2020). Interestingly, speeding can also be observed in real-life online gambling.…”
Section: Relationship Between State and Trait Measures Of Impulsivity...mentioning
confidence: 65%
“…This prediction has been largely corroborated in gambling situations. In real and simulated gambling, as well as in gambling analogue tasks, people tend to initiate a new round more quickly after a loss than after a win (e.g., Chen et al, 2022;Chen et al, 2020;Detez et al, 2019;Ferrari et al, 2022;Stange et al, 2017;Stange et al, 2016) and after a non-gamble outcome (Eben et al, 2020;Verbruggen et al, 2017).…”
Section: Appraising Outcomes In Gamblingmentioning
confidence: 99%
“…A loss that is proximal to a win may indicate a subjectively better current state, and the discrepancy between the current and the desired state might therefore be smaller. Thus, objectively the same outcomes (i.e., losing the same amount of points) were appraised differently, depending on the cues that accompanied the losses (Chen et al, 2020). Some gambling products also include other types of ambiguous outcomes, that may allow for different appraisals.…”
Section: Appraising Outcomes In Gamblingmentioning
confidence: 99%
“…Here we argue that the speed of play might also be a crucial aspect of chasing. Previous work has shown that in simulated gambling or gambling-like tasks in the laboratory, participants initiated a new game more quickly after a loss than after a win [21][22][23][24] and a non-gamble trial [25,26]. The faster initiation of a new gamble after a loss (the so-called post-loss speeding effect [25]) may reflect a stronger urge to continue playing after losing, and can therefore be seen as an expression of loss-chasing [13].…”
Section: Three Expressions Of Within-session Loss-chasingmentioning
confidence: 99%